2018
DOI: 10.2135/cropsci2017.02.0079
|View full text |Cite
|
Sign up to set email alerts
|

Major Management Factors Determining Spring and Winter Canola Yield in North America

Abstract: Canola (Brassica napus L. cv. ‘Canola’) production has both economic and agronomic advantages. The objectives of this review were to summarize the key management factors determining crop productivity and to propose plausible pathways to narrow the gap between actual and potential yield. A synthesis study was conducted on data available from performance trials and by reviewing >100 reports in peer‐reviewed journals, extension publications, and websites. The main outcomes obtained from this synthesis suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 95 publications
3
65
0
1
Order By: Relevance
“…As both years in our study had total precipitation well above 600 mm, it is likely that this did not affect yields in either year. However, in looking at timing of rainfall for spring canola, Hergert et al (2016) identified the need for 1 mm d −1 between emergence and the rosette stage, 2 to 5 mm d −1 between the late rosette and bud stages, and up to 6 mm d −1 at flowering and pod set (Diepenbrock, 2000; Assefa et al, 2018). According to this, September in Year 1 may have been low at 0.6 mm d −1 for emergence and rosette formation and both April (5.2 mm d −1 in Year 1; 2.1 mm d −1 in Year 2) and May (3.6 mm d −1 in Year 1; 4.7 mm d −1 in Year 2) in both years may have had low water availability when flowering and pod set usually occurs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As both years in our study had total precipitation well above 600 mm, it is likely that this did not affect yields in either year. However, in looking at timing of rainfall for spring canola, Hergert et al (2016) identified the need for 1 mm d −1 between emergence and the rosette stage, 2 to 5 mm d −1 between the late rosette and bud stages, and up to 6 mm d −1 at flowering and pod set (Diepenbrock, 2000; Assefa et al, 2018). According to this, September in Year 1 may have been low at 0.6 mm d −1 for emergence and rosette formation and both April (5.2 mm d −1 in Year 1; 2.1 mm d −1 in Year 2) and May (3.6 mm d −1 in Year 1; 4.7 mm d −1 in Year 2) in both years may have had low water availability when flowering and pod set usually occurs.…”
Section: Resultsmentioning
confidence: 99%
“…The difference between our average yield and the US average yield was greatest for Year 2. This may have been caused by the much greater application rates for N, K, and S as soil nutrients and fertilizer are one of the factors with the highest impacts on canola (Assefa et al, 2018). For example, a grain harvest yield of 2074 kg ha −1 for winter canola grown in Kansas had nutrient uptake rates of 157 kg N ha −1 , 132 kg K ha −1 , and 23.5 kg S ha −1 (Ciampitti et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In this line, recent studies in soybean [Glycine max(L.) Merr.] (Corassa et al, 2018;Carciochi et al, 2019), canola (Brassica napus L. "Canola") (Assefa et al, 2018b), and maize (Zea mays L.) (Assefa et al, 2016;Assefa et al, 2018a) classified the data on different YE levels based on its average yield and determined the AOPD at each YE. Therefore, as was observed for canola and soybean (e.g., crops that have compensation mechanisms comparable to wheat), the AOPD in wheat could change across YEs with a greater requirement of plants to attain the maximum yield at the low YE.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass and oil yield of VS were similar to those of FI in 2015 but were lower by 14% in 2016. Canola is a drought-tolerant, low-input oilseed crop and has low ET requirement of 440 mm (Bennett and Harms, 2011;Din et al, 2011;Assefa et al, 2018). Biomass accumulation was greater in treatments receiving irrigation after flowering and most of the post-flowering biomass was partitioned into reproductive parts.…”
Section: Growth-stage-based Irrigation Management On Biomass Yield mentioning
confidence: 99%
“…These species are low in both glucosinolates (<30 mmol g −1 ) and erucic acid (<2%) (Przybylski et al, 2005;Boyles et al, 2012). Canola is a drought-tolerant, low-input oilseed crop and has low ET requirement of 440 mm (Bennett and Harms, 2011;Din et al, 2011;Assefa et al, 2018). Canola oil is the third most consumed vegetable oil around the world after palm (Elaeis guineensis Jacq.)…”
Section: Growth-stage-based Irrigation Management On Biomass Yield mentioning
confidence: 99%